A study on leakage radiation dose at ELV-4 electron accelerator bunker - Md Chulan M.R.; Yahaya R.; Ghazali A.B. (American Institute of Physics Inc., 2023)
Shielding is an important aspect in the safety of an accelerator and the most important aspects of a bunker shielding is the door. The bunker's door should be designed properly to minimize the leakage radiation and shall not exceed the permitted limit of 2.5?Sv/hr. In determining the leakage radiation dose that passed through the door and gaps between the door and the wall, 2-dimensional manual calculations are often used. This method is hard to perform because visual 2-dimensional is limited and is also very difficult in the real situation. Therefore estimation values are normally performed. In doing so, the construction cost would be higher because of overestimate or underestimate which require costly modification to the bunker. Therefore in this study, two methods are introduced to overcome the problem such as simulation using MCNPX Version 2.6.0 software and manual calculation using 3-dimensional model from Autodesk Inventor 2010 software. The values from the two methods were eventually compared to the real values from direct measurements using Ludlum Model 3 with Model 44-9 probe survey meter. © 2014 AIP Publishing LLC.